X^2-2x^2y+3xy^2-6y^3
MitheshShankar:
what do you want us to do with it
Answers
Answered by
10
The given equation is
x³-2x²y + 3xy²- 6y³
= x² (x-2y) + 3y² (x-2y)
= (x²+3y²) (x-2y)
If the equation will be equal to 0, then
x²+3y²=0 or x-2y = 0
x² = -3y² or x = 2y
(2y)²+3y² = 0
4y² + 3y² = 0
7y² = 0
y = 0
Hope it will help you
x³-2x²y + 3xy²- 6y³
= x² (x-2y) + 3y² (x-2y)
= (x²+3y²) (x-2y)
If the equation will be equal to 0, then
x²+3y²=0 or x-2y = 0
x² = -3y² or x = 2y
(2y)²+3y² = 0
4y² + 3y² = 0
7y² = 0
y = 0
Hope it will help you
Similar questions
Hindi,
9 months ago
Social Sciences,
1 year ago